Mechanical Performance of Polypropylene-Wood Fiber Composites: Strength and Microstructure Analysis - ROSDI MD NOOR, MUHAMMAD SYAKIR BIN ROSDI; BINTI MOHD RUS, ANIKA ZAFIAH; M. Akmal A.R.; M. Amirulhusni M. F. (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This research investigates the optimization of injection molding parameters for PP Copolymer and PP Homopolymer, with a focus on the distribution of wood fibers and their influence on the materials’ hardness and strength before and after UV irradiation exposure. By systematically adjusting injection molding parameters, the study aims to achieve optimal wood fiber dispersion within the polymer matrices. The effects of these parameters on the mechanical properties of the composites are evaluated through hardness and strength testing, both pre- and post-UV exposure. The findings of this study provide a comprehensive understanding of the interplay between injection molding conditions, wood fiber distribution, and the mechanical performance of PP Copolymer and PP Homopolymer composites on the durability and stability of these materials under various environmental conditions.